Supervision electricity energy using IoT system / Mohamad Iqhmal Mohd Zaidin ... [et al.] - Mohd Zaidin, Mohamad Iqhmal; Zakaria, Muhamad Zarif Zafrie; Din, Mohamad Asyraf; Ramizu, Muhammad Ammar (Universiti Teknologi MARA, Kedah, 2019)
Objectives. 1. Measuring the amount of current flow in an electric system. 2. Exchange energy consumption to the value of the ringgit (RM). 3. Controlled costing (electric bill). 4. Designed to be easy to move, handle and user-friendly. Novelty / Unique . 1. Communication equipment (ICT) such as computers, phone, tablet and other devices are the important relationships nowadays . 2. The ICT equipment and smart phones available or sold in the market at present complemented by internet access . 3. This project uses the internet as a means of supervised and communication with the electrical system . 4. Measuring the amount of current flow in an electric system and exchange to the value of the ringgit (RM). 5. Any electrical equipment which are home, office, factory and which alone can monitor dan controlled by using equipment this is designed. Originality / Special criteria This project uses the internet as a means of supervised and communication with the electrical appliances. Measuring the amount of current flow in an electric system and exchange to the value of the ringgit (RM). Display the values (RM) on ICT equipment.